APLIKASI KOMPOS VINASSE DAN BAKTERI ENDOFIT UNTUK MEMPERBAIKI SERAPAN NITROGEN DAN PERTUMBUHAN TANAMAN TEBU (Saccharum officinarum L.) - Ina Pratiwi; Dias Gustomo; Zaenal Kusuma (Jurnal Tanah dan Sumberdaya Lahan, 2018)
Nitrogen is a macro nutrient need by plants to enhance growth and productivity. Nitrogen element can be supplied through inorganic fertilizer, compost or biological fertilizer. The purpose of this study was to analyze the effect of vinasse compost and endophyte bacteria of Klebsiella sp. on nitrogen uptake and sugarcane growth. The treatments tested in this study were K0 = control (no compost vinasse and Klebsiella sp.), P1 = (Klebsiella sp. + 75% ZA + 25% vinasse compost), P2 (Klebsiella sp. + 50% ZA + 50% vinasse compost), P3 (Klebsiella sp. + 100% ZA fertilizer + 0% vinasse compost), P4 (without inoculation of Klebsiella sp. + 75% ZA + 25% vinasse compost), P5 (without inoculation of Klebsiella sp. + 50% ZA + 50% Vinasse compost). The treatments were arranged in a completely randomized design with five replicates. The results showed that endophyte bacteria could only enter in P1 treatment. The total N-content, N-available and N-absorption were associated with P1 treatment. Vegetative growth of sugarcane did not show significant different. The P1 treatment had the highest value of plant height and number of leaves. As for the number of tillers, on 4 terms, the highest value was observed on P2 treatment.